Factors Affecting the Economics Learning Outcomes: Discipline Character, Learning Motivation, and Teaching Variations - Suratno; Ekawarna; Rachmad; Suardi (LPPM Undiksha, 2023)
The success or failure of a student in education depends on the learning process experienced by the student. The teachers can provide more varied learning in order to improve student learning outcomes. This study aims to analyze the influence of the character of discipline and learning motivation as well as variations in teaching on the economics learning outcomes of students in grade X. The type of research used is explanatory research with survey method. The population in the study were all students in class X high school, using random sampling so that the research sample was all participants in class X high school. The research instrument used in this study was a questionnaire while the learning outcomes were taken from the student's learning scores. The data analysis technique in this study is to use path analysis (path analysis) in its implementation is carried out through the SPSS program. There is an influence between student characters on student learning outcomes. The character of discipline and learning motivation have a positive effect on student learning outcomes because learning outcomes will increase if the character of learning discipline increases and is followed by learning motivation and student learning outcomes can be bad if students are not instilled with the character of discipline and motivation in learning. Variations given by the teacher can develop student learning outcomes if they have various kinds of teaching variations.